The Role of Dietary Fiber in Rheumatoid Arthritis Patients: A Feasibility Study - Häger, Julian; Bang, Holger; Hagen, Melanie; Frech, Michael; Träger, Pascal; Sokolova, Maria V.; Steffen, Ulrike; Tascilar, Koray; Sarter, Kerstin; Schett, Georg; Rech, Jürgen; Zaiss, Mario (Nutrients, 2019)
Short-chain fatty acids are microbial metabolites that have been shown to be key regulators of the gut-joint axis in animal models. In humans, microbial dysbiosis was observed in rheumatoid arthritis (RA) patients as well as in those at-risk to develop RA, and is thought to be an environmental trigger for the development of clinical disease. At the same time, diet has a proven impact on maintaining intestinal microbial homeostasis. Given this association, we performed a feasibility study in RA patients using high-fiber dietary supplementation with the objective to restore microbial homeostasis and promote the secretion of beneficial immunomodulatory microbial metabolites. RA patients (n = 36) under routine care received daily high-fiber bars or cereals for 28 days. Clinical assessments and laboratory analysis of immune parameters in blood and stool samples from RA patients were done before and after the high-fiber dietary supplementation. We observed an increase in circulating regulatory T cell numbers, favorable Th1/Th17 ratios, as well as decreased markers of bone erosion in RA patients after 28 days of dietary intervention. Furthermore, patient-related outcomes of RA improved. Based on these results, we conclude that controlled clinical studies of high-fiber dietary interventions could be a viable approach to supplement or complement current pharmacological treatment strategies.
CRIS-Team Scopus Importer:2019-10-18
Keywords: gut–joint axis; high-fiber diet (HFD); microbiota; rheumatoid arthritis (RA); short chain fatty acids (SCFA)